Titel prent: Klassenstrijd : christelijk arbeider: Ik wil geen strijd, ik wil samenwerking. Kapitalist: Groot gelijk man - Hahn, Albert
Titel prent: Klassenstrijd : christelijk arbeider: Ik wil geen strijd, ik wil samenwerking. Kapitalist: Groot gelijk man...